2003
DOI: 10.1007/s00125-003-1117-5
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte growth factor and beta-cell differentiation in human fetal pancreatic endocrine precursor cells

Abstract: Aims and hypothesis. Keratinocyte growth factor (KGF) is a member of the heparin-binding fibroblast growth factor family with a high degree of specificity for epithelial cells in vitro and in vivo. Our aim was to study the effect of KGF on beta-cell growth and differentiation on islet-like cell clusters derived from human fetal pancreas. Methods. We investigated the effects of KGF, in vitro, on beta-cell differentiation from undifferentiated pancreatic precursor cells and in vivo after transplantating human fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 41 publications
4
34
0
Order By: Relevance
“…Another group has recently shown that FGF7 treatment activated beta cell development from human fetal pancreatic cell preparations grafted to athymic rats. No ef- fect of FGF7 was seen in vitro, suggesting that the growth effect of FGF7 was indirect [10]. Here, we show that FGF7 and FGF10 also have a direct effect on embryonic pancreatic cells.…”
Section: Discussionmentioning
confidence: 60%
“…Another group has recently shown that FGF7 treatment activated beta cell development from human fetal pancreatic cell preparations grafted to athymic rats. No ef- fect of FGF7 was seen in vitro, suggesting that the growth effect of FGF7 was indirect [10]. Here, we show that FGF7 and FGF10 also have a direct effect on embryonic pancreatic cells.…”
Section: Discussionmentioning
confidence: 60%
“…A possible explanation for the greater effect of KGF on b-cell differentiation in diabetic rats is the context of restricted b-cell mass in those rats, which implies the activation of several interconnected compensatory mechanisms in the pancreas in order to regulate cell homeostasis. In keeping with this idea, we have previously shown that KGF administration to nude rats bearing transplant composed of fetal endocrine pancreatic precursor cells led to the increase in the total number of b-cells in the graft without increasing the b-cell number within the pancreas of adult non-diabetic rats (Movassat et al 2003). In order to elucidate whether KGF is able to stimulate b-cell growth in neonatal rats with spontaneous b-cell deficiency, we are currently investigating the effect of an early postnatal treatment of Goto-Kakizaki rats with KGF on the b-cell growth.…”
Section: Discussionmentioning
confidence: 84%
“…In the pancreas, KGF and its receptor are upregulated in pancreatic carcinomas (Ishiwata et al 1998) and ectopic expression of KGF in b-cells resulted in intra-islet duct cell proliferation (Krakowski et al 1999). Moreover, KGF stimulates differentiation of endocrine precursor cells isolated from human fetal pancreas into b-cells (Movassat et al 2003). Here, we investigated the impact of an early treatment of non-diabetic and diabetic rat neonates with KGF (palifermin) on the regulation of b-cell growth and regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these factors are well known to stimulate beta cell growth in vitro [11,[23][24][25][26][27][28]. Further support for a possible gastrin-independent mechanism for the increased beta Fig.…”
Section: Discussionmentioning
confidence: 91%